Isolation and characterization of lactic acid bacteria from Apis mellifera stomach and their potential as antibacterial using in vitro test against growth of Staphylococcus aureus and Salmonella typhimurium - Ana Bila Nadia; Siti Nur Jannah; Susiana Purwantisari (NICHE Journal of Tropical Biology, 2020)
Food contaminated by pathogenic bacteria is very dangerous to consume especially if the bacteria can produce toxins. Staphylococcus aureus andSalmonella typhimurium are two examples of pathogenic bacteria that cause demage to food because they produce enterotoxins that can cause food poisoning to consumers. The use biological agents as antibacterial agents can be used as a solution to overcome this. Lactic acid bacteria (LAB) can produce compounds thet can inhibit the growth of pathogenic bacteria in food. This study aims to obtain local LAB isolates from the stomach of Apis mellifera in Indonesia and determine their characteristics as potential biopreservatif foods, to test the inhibition of LAB bacteriocin against Staphylococcus aureus and Salmonella typhimurium in vitro. The isolation method was carried out using multilevel dilution and streak plates on MRSA media. Morphological identification was carried out macroscopically on BAL and microscopic colonies with gram staining. Antibacterial test using the well method. LAB isolation result obtained eight isolatates. Antibacterial activitytest results for cells, all isolates showed inhibition of   Staphylococcus aureus and Salmonella typhimurium, for further antibacterial testing using 2 potential isolates namely PAM 3 and PAM 4. The two isolates were further tested for antibacterial with cell free supernatant using two treatments namely pH acidic and neutral, both isolates showed antibacterial activity at acidic ph better than neutral ph, wheares for the bacteriosin analysis test all isolates had no inhibition.